Differences between TripAdvisor and Booking.com in branding co-creation - Borges-Tiago, Maria Teresa (2021)
Teresa Borges-Tiago, M., Arruda, C., Tiago, F., & Rita, P. (2021). Differences between TripAdvisor and Booking.com in branding co-creation. Journal of Business Research, 123, 380-388. https://doi.org/10.1016/j.jbusres.2020.09.050 ---%ABS3%